2021
DOI: 10.1097/md.0000000000027658
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of acupuncture combined with Chinese herbal medicine in the treatment of type 2 diabetes mellitus

Abstract: Background: Diabetes has become a global public health problem and danger to human health. Diabetes is the main cause of blindness, kidney failure, heart attack, stroke, and lower limb amputation. According to the latest epidemiological survey and research, the overall prevalence of diabetes in mainland China is 11.2%, of which type 2 diabetes mellitus (T2DM) accounts for more than 90% acupuncture combined with Chinese herbal medicine have been widely used in the treatment of T2DM. However, we have not found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Diabetes has become a global public health problem and a threat to human health [ 46 , 47 ]. The drugs currently on the market to treat diabetes have the capability of lowering blood glucose, eliminating clinical symptoms, and delaying the onset of complications for a short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes has become a global public health problem and a threat to human health [ 46 , 47 ]. The drugs currently on the market to treat diabetes have the capability of lowering blood glucose, eliminating clinical symptoms, and delaying the onset of complications for a short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…In a monotherapy study, metformin was compared with sulfonylureas and meglitinides showed increased risk to cardiovascular complications in T2DM [ 148 ]. In a meta-analysis study, acupuncture combined with Chinese herbal treatment showed positive therapeutic openings in T2DM [ 149 ]. The treatment using ipragliflozin has shown adverse effects causing genital infections in T2DM patients [ 150 ].…”
Section: Traditional Indian Medicinal Plants To Treat T2dm and Pdmentioning
confidence: 99%
“…In ancient traditional Chinese medicine, acupuncture and Chinese herbal medicine were believed to balance Yin and Yang, harmonize qi and blood, and unblock meridian and collateral. 15 In recent years, acupuncture combined with Chinese herbal medicine has made great progress in treating motor neuron disease, 16 angina pectoris of coronary heart disease, 17 non-alcoholic fatty liver disease, 18 type 2 diabetes mellitus, 19 osteoporosis, 20 Gouty Arthritis 21 and so on. Shi's orthopedics and traumatology academic school, one of Traditional Chinese medicine (TCM) schools, also has done some researches in this area.…”
Section: Introductionmentioning
confidence: 99%